Total and free zinc dynamics as biomarkers for neurological impairment in traumatic spinal cord injury - Heller, Raban; Maares, Maria; Chillon, Thilo Samson; Witte, Hanno; Alhalabi, Obada; Heene, Stefan; Younsi, Alexander; Haubruck, Patrick; Schomburg, Lutz; Moghaddam-Alvandi, Arash; Biglari, Bahram; Haase, Hajo (Nutrients, 2025)
Background/Objectives: Traumatic spinal cord injury (TSCI) profoundly impacts patients by precipitating a loss of motor and sensory capabilities, largely due to oxidative stress and inflammation during the secondary injury phase. Methods: This investigation explores the diagnostic potential of zinc (Zn) and free zinc (fZn) as biomarkers by analyzing their serum concentration dynamics in 48 TSCI individuals with TSCI, with the aim of correlating these levels with neurological impairment. Serum samples collected at admission, 4 h, 9 h, 12 h, 24 h, and 3 days post-injury were analyzed for total serum Zn and fZn concentrations. The patients were compared to a control group comprised of individuals with vertebral fractures but no neurological deficits. Results: The study revealed injury-specific fluctuations in Zn and fZn levels following TSCI, with significantly lower Zn levels observed post-TSCI compared to controls (p = 0.016). The American Spinal Injury Association (ASIA) Impairment scale (AIS) assessments at admission and three months post-injury showed Zn level differences are linked to neurological recovery (AIS+:1 > AIS+:2, 0 h: p = 0.008; AIS+:0 < AIS+:1, 4 h: p = 0.016), highlighting the critical role of Zn and trace elements in the early remission process after TSCI. Notably, significant differences in fZn levels were detected between the control and TSCI groups (TSCI < Control; 12 h: p = 0.045; 24 h: p = 0.001; 3 d: p = 0.016), with the peak diagnostic performance of fZn at 24 h post-injury, as indicated by an Area Under the ROC Curve (AUC) of 83.84% (CI: 0.698-0.978). Conclusions: These findings underscore the potential of fZn as a biomarker to guide early diagnostic and therapeutic interventions aimed at mitigating secondary injury and enhancing recovery outcomes. This study contributes insights into the dynamics of serum Zn and its importance, holding specific diagnostic properties that could be critically relevant in the early phase of biomarker signature development for TSCI diagnostics and prognosis.
Gesehen am 04.08.2025